A Single Dose of Benzathine Penicillin G Is as Effective as Multiple Doses of Benzathine Penicillin G for the Treatment of HIV-Infected Persons With Early Syphilis - Ganesan, Anuradha (Clin Infect Dis, 2015)
Background. Treatment guidelines recommend the use of a single dose of benzathine penicillin G (BPG) for treating early syphilis in human immunodeficiency virus (HIV)-infected persons. However, data supporting this recommendation are limited. We examined the efficacy of single-dose BPG in the US Military HIV Natural History Study. Methods. Subjects were included if they met serologic criteria for syphilis (ie, a positive nontreponemal test [NTr] confirmed by treponemal testing). Response to treatment was assessed at 13 months and was defined by a ≥4-fold decline in NTr titer. Multivariate Cox proportional hazard regression models were utilized to examine factors associated with treatment response. Results. Three hundred fifty subjects (99% male) contributed 478 cases. Three hundred ninety-three cases were treated exclusively with BPG (141 with 1 dose of BPG). Treatment response was the same among those receiving 1 or >1 dose of BPG (92%). In a multivariate analysis, older age (hazard ratio [HR], 0.82 per 10-year increase; 95% confidence interval [CI], .73–.93) was associated with delayed response to treatment. Higher pretreatment titers (reference NTr titer <1:64; HR, 1.94 [95% CI, 1.58–2.39]) and CD4 counts (HR, 1.07 for every 100-cell increase [95% CI, 1.01–1.12]) were associated with a faster response to treatment. Response was not affected by the number of BPG doses received (reference, 1 dose of BPG; HR, 1.11 [95% CI, .89–1.4]). Conclusions. In this cohort, additional BPG doses did not affect treatment response. Our data support the current recommendations for the use of a single dose of BPG to treat HIV-infected persons with early syphilis.